Large‐scale sequencing studies expand the known genetic architecture of Alzheimer's disease. Issue 1 (31st December 2021) - Xue, Diane; Bush, William S.; Renton, Alan E.; Marcora, Edoardo A.; Bis, Joshua C.; Kunkle, Brian W.; Boerwinkle, Eric; DeStefano, Anita L.; Farrer, Lindsay; Goate, Alison; Mayeux, Richard; et al.
Abstract: Introduction: Genes implicated by genome‐wide association studies and family‐based studies of Alzheimer's disease (AD) are largely discordant. We hypothesized that genes identified by sequencing studies like the Alzheimer's Disease Sequencing Project (ADSP) may bridge this gap and highlight shared biological mechanisms. Methods: We performed structured literature review of genes prioritized by ADSP studies, genes underlying familial dementias, and genes nominated by genome‐wide association studies. Gene set enrichment analyses of each list identified enriched pathways. Results: The genes prioritized by the ADSP, familial dementia studies, and genome‐wide association studies minimally overlapped. Each gene set identified dozens of enriched pathways, several of which were shared (e.g., regulation of amyloid beta clearance). Discussion: Alternative study designs provide unique insights into AD genetics. Shared pathways enriched by different genes highlight their relevance to AD pathogenesis, while the patterns of pathway enrichment unique to each gene set provide additional targets for functional studies.